Biochemical markers in differentiating gallstones pancreatitis from non-gallstone pancreatitis - Alghamdi, Masoud; Alrashdi, Afnan Hassan; Almaghamsi, Addi Hatem; Alamri, Atif Essa; Abdulrashid, Bushra Ahmad; Sabban, Zaini Mohammedsaeed; Alhassan, Abdullah Lafi; Alanazi, Fahad Salem; Abanmi, Sulaiman Abdelaziz; Alghamdi, Fayez Dhyefallah; Alshammari, Layla Khalid; Hussein, Al-Hassan Mohammed Ba (International Journal Of Community Medicine And Public Health, 2021)
Acute pancreatitis has many causes; however, the most common cause of pancreatitis is gallstones globally. We have searched for relevant studies in this field aiming at establishing a short review about the usefulness of biomarkers in the diagnosis of acute pancreatitis and the relevant biomarkers and tests that can differentiate acute gallstone pancreatitis from other etiologies. It is worth mentioning that for the diagnosis and prognosis of biliary pancreatitis, radiological and laboratory diagnosis plays a major role in this field. Three biomarkers including serum amylase, lipase, and trypsinogen are the most important and most frequently noticed biomarkers in association with acute pancreatitis. Serum amylase has a specificity rate of 95% and a sensitivity of 61% when it measures more than 1000 IU/l which is three times as high as the normal level. However, it can be also found in other intrabdominal inflammatory conditions, and therefore, it cannot be used alone in the diagnosis. It has been reported that the specificity and sensitivity were 95% and 94%, respectively, for detecting high trypsinogen-2 levels in the patients’ urinary samples, which were indicative of acute pancreatitis. For the diagnosis of biliary pancreatitis, liver function tests should be assessed. Although they might be specific, they are not always diagnostic in some cases, and therefore, other approaches for detecting gallstones as ultrasonography and MRCP should be considered together with the liver enzymes for an appropriate diagnosis.